Composite nanolubricants in automotive air conditioning system: An investigation on its performance - N. N. M., Zawawi; Azmi, W. H.; Sharif, M. Z.; Shaiful, A. I. M. (IOP Publishing, 2019)
AAC system is an important and necessary system in a vehicle in giving thermal comfort to the automotive cars passenger by reducing the surrounding temperature. The experimental investigation on performance of AAC system using composite nanolubricant provides useful data for future development of automotive cars due to its efficiency in improving the system performance. The AAC test bench was developed and utilized from Perodua Kancil. Cooling capacity, compressor work and coefficient of performance (COP) of AAC system using pure lubricant and Al2O3-SiO2/PAG composite nanolubricants had been investigated at different refrigerant charges (95 to 155g) and different speeds (900 to 2100 rpm). The result shows that the cooling capacity and COP of composite nanolubricants increased compared to pure lubricant. Meanwhile, the compressor work was reduced. Cooling capacity and COP are relatively increased by 59.91% and 7.72% respectively compared to based lubricant. The maximum reduction achievement for compressor work is by 9.35% with 155g refrigerant charge and at 2100 rpm. Therefore, Al2O3-SiO2/PAG composite nanolubricants is recommended to be used as the compressor lubrication to enhance AAC performances system.